ANALISIS WACANA KRITIS POLEMIK UU CIPTA KERJA - Azizah, Hilma Azmi; Triyono, Sulis (Sunan Kalijaga State Islamic University Yogyakarta, 2021)
This study aims to examine the Theo van Leeuwen model of inclusion and exclusion strategies used by the online media detikcom, KOMPAS.com, Serambinews.com, and CNN Indonesia. This type of research is qualitative research using descriptive methods. The data used in this study are phrases, clauses, and sentences in the four online media companies that address the polemic against the Job Creation Act. The instrument of this research is the researcher himself assisted by other supporting instruments such as books and supporting articles regarding Theo van Leeuwen’s theory. The data collection methods used were reading and note-taking techniques. The analytical method used is the observation method. The advanced technique uses free, engaged listening. The results of the study are as follows (1) inclusion strategy in online media detikcom, KOMPAS.com, Serambinews.com, and CNN Indonesia includes passivation, nominalization, and substitute clauses, (2) exclusion strategy in online media detikcom, KOMPAS.com, Serambinews.com, and CNN Indonesia include objectivation-abstraction, nomination-categorization, nomination-identification, assimilation-individualization, and association-dissociation.